DISKURSUS KEISLAMAN DI LEMBAGA PENDIDIKAN TINGGI: KAJIAN ISLAM DI SPs UIN SYARIF HIDAYATULLAH JAKARTA - Nurtawab, Ervan; Syaripudin, Syaripudin, (JURNAL TAPIS, 2011)
Islamic educational institution in Southeast Asia, especially in Indonesia, has long history of its development. It begins when Islam itself had been initially introduced to the region. By the mid of 20th century, people witnessed the formative period of Islamic higher educational institutions. This article seeks to describe how Islam has been scholarly taughtâand of course learnedâin higher educational level, specifically in MA and Ph.D. degrees. The writers limit its area of study only to look at Islamic studies as has been developed in Graduate School (SPs) Syarif Hidayatullah State Islamic University (UIN) Jakarta within the las five years.Keywords: Kajian Islam, integrasi keilmuan, pendidikan tinggi, pascasarjana